2005
DOI: 10.1115/1.2118687
|View full text |Cite
|
Sign up to set email alerts
|

A More General Mobility Criterion for Parallel Platforms

Abstract: This contribution presents a more general mobility criterion applicable to parallel platforms, unlike previously employed mobility criteria based on the well-known Kutzbach-Grübler criterion that often fails to provide the correct number of degrees of freedom of parallel manipulators, the mobility criterion introduced in this contribution provides the correct number of degrees of freedom for a wider class of parallel manipulators. Furthermore, the analysis provides insight into why the criteria based on the Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Taking into account that the SPM is composed of seven links, two revolute pairs, two prismatic pairs, one universal joint, and three spherical joints, then the resulting dof of the proposed SPM is three. Moreover, it can be shown that this SPM is an exceptional platform according with the classification proposed in Rico et al [20].…”
Section: A Family Of Spms Composed Of Two Legsmentioning
confidence: 94%
“…Taking into account that the SPM is composed of seven links, two revolute pairs, two prismatic pairs, one universal joint, and three spherical joints, then the resulting dof of the proposed SPM is three. Moreover, it can be shown that this SPM is an exceptional platform according with the classification proposed in Rico et al [20].…”
Section: A Family Of Spms Composed Of Two Legsmentioning
confidence: 94%
“…The mobility can also be found by the motion space as in Rico et al [6] [7]. The degree of freedom of the motion of the end effector is first found.…”
Section: Introductionmentioning
confidence: 99%
“…First, we use Grübler's formula or a generic method based on the results in Rico et al [6] [7] to verify whether the manipulator, considering the passive joints only, generates a non-trivial motion. This is based on the results found in From and Gravdahl [14].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al implemented Herve's theory (under the name of displacement manifold) in classification and synthesis of 5 dof parallel mechanisms [15]. On the mobility analysis side, Rico's work on single closed loop [16] and parallel mechanisms [17] are also applications of Herve's theory. However, Rico's work was less general and thus did not gain much popularity in comparison to screw theory based method.…”
mentioning
confidence: 97%